Analysis of 3D printed stack in thermoacoustic cooling - Roslan, Muhammad Nazmi Hadi (Joint Journal of Novel Carbon Resource Sciences and Green Asia Strategy, 2021)
Inconsistencies in fabricated thermoacoustic stacks are due to the methods available to obtain the desired geometry and dimensions even under optimized design parameters. This paper presents performance results from stacks fabricated using 3D printing technology which minimizes the error, disposes of irregularities and can reduce production time. In this study, the performance of a thermoacoustic refrigerator was determined from measurements of the temperature difference across various 3D printed stack lengths fabricated. Experiments were done at 400 Hz frequency with different stack plate spacing and thickness, in a 21-mm diameter resonator. Results show that a 0.7 mm stack plate spacing with a 0.5 mm plate thickness performed better compared to those with smaller spacing at the same thickness or with the same spacing but larger thickness. The outcomes of this study have shown the need for the fabrication technology to keep pace with optimized design to realize global efforts towards a sustainable environment.